The National Organic Standards Training Materials: Trainer's Manual - Mickie E. Swisher; Rose Koenig (EDIS)
This publication is only available in PDF format. The following is a brief overview of the Trainer's Guide and the links to the eight modules. This document is FCS8794, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date April 6, 2006.